Hepatitis C virus: epidemiology and genotypes in the north east of England. Issue 2 (February 1996) - Watson, J P; Brind, A M; Chapman, C E; Bates, C L; Gould, F K; Johnson, S J; Burt, A D; Ferguson, J; Simmonds, P; Bassendine, M F
Abstract : The epidemiology of hepatitis C virus (HCV) infection was studied in an English teaching hospital over an 18 month period. A total of 104 HCV antibody positive patients were referred for further investigation. They were divided into those diagnosed through screening (blood donors and intravenous drug abusers) and those diagnosed for other reasons, and their mean ages, known risk factors for HCV transmission, genotypes, and liver biopsy histology were analysed. Screened patients were significantly younger than the others. No significant difference in age was found between genotypes. Most patients genotyped (69%) were genotype 1. Intravenous drug abusers had a higher proportion of subtype 1a, and patients who acquired HCV through blood transfusion had a higher proportion of subtype 1b. Liver biopsy specimens were scored using a histological activity index for liver inflammation and fibrosis. Patients with subtype 1b had significantly more severe liver disease than other genotypes when the histological activity index scores for fibrosis were analysed (p < 0.05). Liver disease worsened significantly with age according to all three histological activity index scores (portal activity: p < 0.01, acinar activity: p < 0.001, fibrosis: p < 0.0001). Liver disease worsened with increased duration of infection (p < 0.002), and patients who also abused alcohol presented at a significantly younger age (cirrhosis, p < 0.05, hepatocellular carcinoma, p < 0.02).